Review and assessment of rural development programmes in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Review and assessment of rural development programmes in Africa 1996 126pp ISBN 92 9081 1404 published jointly by CTA and CIRDAFRICA Available from CTA